A novel methodology for comprehensive planning of battery storage systems - Arévalo, Paul; Tostado-Véliz, Marcos; Jurado, Francisco (Journal of energy storage, 2021)
•A novel methodology for comprehensive planning of battery storage systems is proposed.•Original combination of the software HOMER pro and Gurobi.•A techno-economic analysis of different batteries technologies.•Real data is temporally represented in the form of representative days..•Lead-Acid and NaS technologies resulted the most profitable BSS projects. Battery storage system design has become a crucial task for nanogrids and microgrids planning, as it strongly determines the techno-economic viability of the project. Despite that, most of developed methodologies for optimally planning this kind of systems still present some important issues like high computational burden or insufficient results. This paper develops a novel methodology for battery storage system planning in nanogrids and microgrdis, which aims at overcoming the main issues presented by other methodologies. To achieve this goal, our proposal originally combines different software, clustering techniques and optimization tools. As salient features of the developed approach, it is worth remarking its efficiency, versatility, ability to manage with different time horizons and comprehensiveness. A prospective nanogrid in the region of Cuenca, Ecuador, serves as illustrative case study to show the capabilities, efficiency and effectiveness of the proposed approach as providing sufficient guidelines for its universal applicability. Among other relevant results, our proposal is able to determine that, for the studied grid, the daily operating cost can be reduced up to 17% by using Nickel-Cadmium batteries, however, the usage of Lead-Acid and Sodium-Sulfur technologies resulted more attractive through the project lifetime due to their longer lifetimes and relatively low capital costs.